EDUKASI DIET DIABETES MELLITUS BERBASIS APLIKASI BERPENGARUH TERHADAP PENGETAHUAN PASIEN RAWAT JALAN DIABETES MELLITUS TIPE 2 - Yuniarti Yuniarti; Mohammad Jaelani; Arintina Rahayuni; Risna Yuliasita; Musfiatul Nur Laila (JURNAL RISET GIZI, 2020)
Background: There are 4 pillars of diabetes mellitus management, namely education, medical nutrition therapy (meal planning), physical exercise and pharmacological intervention. The failure of Diabetes Mellitus patients in treatment is caused by various factors, including not having a good diet, so a special approach is needed for Diabetes Mellitus patients through nutrition education based on the Diabetes Mellitus Diet Application to increase knowledge and dietary compliance of Diabetes Mellitus patients. Objective: To determine the effect of application-based Diabetes Mellitus diet education on knowledge and dietary compliance in Type 2 Diabetes mellitus patients. Methods: Quasi-experimental research design was pre-post test control group design with 45 case groups and 45 control groups. Sampling was purposive sampling using inclusion and exclusion criteria. Research at the Outpatient Polyclinic of RSUD KRMT Wongsonegoro Semarang City, in August-October 2019. Data analysis used Paired t test, the analysis is significant if the p value is less than 0.05 with a significance range of 95%. Result: Increasing knowledge but unable to improve dietary compliance with confounding factors is education and significantly different (p = 0.000). Conclusion : It affects the patient's diet knowledge but does not affect dietary adherence, so that it can guarantee the quality of life of Diabetes Mellitus Patients, therefore this activity needs to be carried out and the application can be applied especially to patients and families and hospital institutions as a medium for education.